Evaluasi Karakter Agro-Morfologi pada 20 Genotipe Hasil Seleksi Temu Hitam (Curcuma aeruginosa Roxb.) - Nurcholis, Waras; Hartanti, Hartanti; Suryani, Suryani; Priosoeryanto, Bambang Pontjo (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2019)
The present study aimed to evaluate different agro-morphological traits among twenty genotypes of Curcuma aeruginosa Roxb. and three varieties of Curcuma zanthorrhiza Roxb. Agro-morphological data traits were investigated based on qualitative and quantitative parameters from PPVFRA descriptors with modification. All the recorded data was analyzed through SPSS 16.0 and R 3.4.2 for ANOVA and similarity analysis, respectively. Significant differences (P <0.05) were observed in the traits studied of the habit of the rhizome, the shape of the rhizome, length of primary rhizome, number of mother rhizome, plant height, pseudostem diameter, number of leaves, leaf length, leaf width, and number of shoots. Hierarchical cluster analysis (HCA) classified the genotypes into three groups. The principal component analysis (PCA) were showed consistent with results of the HCA. These genotypes could be used as novel genotype in agricultural biochemistry for breeding programs.